Cultural resilience and economic recovery: Evidence from Hurricane Katrina - Iftekhar Hasan; Stefano Manfredonia; Felix Noth (Halle Institute for Economic Research (IWH), 2020)
This paper investigates the critical role of culture for economic recovery after natural disasters. Using Hurricane Katrina as our laboratory, we find a significant adverse treatment effect for plant-level productivity. However, local religious adherence and larger shares of ancestors with disaster experiences mutually mitigate this detrimental effect from the disaster. Religious adherence further dampens anxiety after Hurricane Katrina, which potentially spur economic recovery. We also detect this effect on the aggregate county level. More religious counties recover faster in terms of population, new establishments, and GDP.
Keywords: E23; E32; Z12; 330; natural disasters; plant-level productivity; religion; recovery